PENGARUH INSENTIF DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. ESTA DANA VENTURA CABANG CIPUTAT KOTA TANGERANG SELATAN - Mita Sari, Renda; Saprudin, Udin (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to find out the influence of incentives and motivation on employee performance at PT Esta Dana Ventura Ciputat Branch, both partially and simultaneously. The method used in this research is a quantitative descriptive method. The sampling technique used was a saturated sampling technique with a sample of 60 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, descriptive analysis, simple regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research are that incentives have a significant effect on employee performance with the regression equation Y = 19,530 + 0.572 .8% is influenced by other factors. Hypothesis testing obtained a calculated t value > t table or (6.773 > 2.002). Thus, H0 is rejected and Ha is accepted, meaning that there is a significant influence between incentives on employee performance. motivation has a significant effect on employee performance with the regression equation Y = 9.678 + 0.760 influenced by other factors. Hypothesis testing obtained a calculated t value > t table or (10.911 > 2.002). Thus, H0 is rejected and Ha is accepted, meaning that there is a significant influence between motivation and employee performance. incentives and motivation have a significant effect on employee performance with the regression equation Y = 8.725 + 0.141 X1 + 0.652 X2. The correlation coefficient value or level of relationship between the independent variable and the dependent variable is 0.828, meaning it has a very strong relationship with the value of the coefficient of determination or simultaneous influence contribution of 0.686 or 68.6% while the remaining 31.4% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (62.173 > 2.766). Thus H0 is rejected and Ha is accepted. This means that there is a significant simultaneous influence between incentives and motivation on employee performance at PT Esta Dana Ventura Ciputat Branch, South Tangerang.